The Influence of Social Factors on Mobile Phone Purchasing Decisions Study on Guffy Cell Karangjati Consumers - Indah Sari Humendru; Tri Maryani (Mahesa Research Center, 2025)
This study aims to analyze the influence of social aspects on mobile phone purchasing decisions at Guffy Cell, a retail store that sells various brands of mobile phones in Karangjati, Bergas District, Semarang Regency. The focus of this study is how the influence of family, peers, social status, and trends affect consumer preferences in choosing mobile phones. Data were collected through structured questionnaires distributed to 100 respondents and analyzed using multiple linear regression. The results showed that social dynamics significantly shape purchasing decisions, with friend recommendations being the most dominant factor. Social status and trends also have a significant impact, reflecting consumers' tendency to choose mobile phones that match their self-image and trend developments. Meanwhile, a family influence still contributes, although to a lesser extent. This research model explains almost 50% of the variability in purchasing decisions, as indicated by the R value of 48.5%, indicating a substantial role for social elements in consumer behavior. These findings confirm that mobile phone purchasing decisions are not only based on price or technical features but are also influenced by the social environment. The implication is that business actors can optimize marketing strategies by utilizing communities, reference groups, and current trends to increase customer engagement and sales.